Why is the Doha Development agenda failing? And what can be done? A computable general equilibrium-game theoretical approach - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2017)
The objective of this chapter is to provide a strategic analysis of these negotiations. In particular, we examine whether these trade negotiations can reach a pro-liberalization outcome, and if so, which packages may be approved. If no pro-liberalization outcome is possible, we ask the following questions: Which countries are preventing the achievement of an agreement, and why? Is there any way to change the negotiation rules to achieve a pro-liberalization outcome? How can we explain the creation of coalitions, and do they thwart the success of the negotiations?